Long-term adoption of bed planted conservation agriculture based maize/cotton-wheat system enhances soil organic carbon stabilization within aggregates in the indo-gangetic plains - Joseph, Ann Maria; Bhattacharyya, Ranjan; Biswas, D. R.; Das, T. K.; Bandyopadhyay, K. K.; Dey, Abir; Ghosh, Avijit; Roy, Plabani; Naresh Kumar, Soora; Jat, S. L.; Casini, Ryan; Elansary, Hosam O.; et al. (Frontiers in Environmental Science, 2023)
Sustainability of contemporary crop establishment and management practices is questioned due to soil degradation, higher carbon emission and declining soil productivity. Hence, this study was conducted to address the impacts of conservation agriculture (CA) practices like permanent broad beds (PBB), permanent narrow beds (PNB) and zero tilled flat beds (ZT) with residue retention on soil organic carbon (SOC) protection within aggregates in the Indo-Gangetic Plains (IGP).Compared to conventionally tilled (CT) plots, the total SOC content was ∼27-33% higher in the CA plots on equivalent mass basis. The soil physical properties, such as soil aggregation and mean weight diameter were considerably improved under the CA practices. The macroaggregates were ∼41, 37 and 27% higher in the PBB with residue (PBB+R), PNB with residue (PNB+R) and ZT with residue (ZT+R) plots (CA plots), respectively, than the CT plots in the surface soil (0-15 cm). The plots under PBB+R had ∼31% higher microaggregates within macroaggregates than the CT plots (24.4 g 100 g -1 ) soil. An increase in SOC content by ∼72, 55 and 69% was observed in the PBB+R, PNB+R and ZT+R plots over the CT plots in microaggregates within macroaggregates (3.02 Mg ha -1 ). However, plots under PBB+R, PNB+R and ZT+R had only ~11, 3 and 23% more SOC within silt+clay fraction, respectively, than CT plots (5.85 Mg ha -1 ). Thus, SOC stabilization within microaggregates inside macroaggregates was the major mechanism, and not the chemical stabilization within silt+clay, of C sequestration under CA. As aggregate-associated carbon is an ecosystem property that strongly affects organic carbon stabilization, water holding capacity and resistance to erosion, growing maize/cotton-wheat system under PBB+R practice is a viable option for carbon sequestration in the IGP and similar agro-ecologies.